Percaya tapi Tidak Percaya: Studi Kasus pada Unit Simpan Pinjam KUD Margodadi Desa Sukamaju - Elsa Pramesti; Rina Susanti (Laboratory of Anthropology Department, Faculty of Humanity, Halu Oleo University, 2024)
KUD Margodadi savings and loan unit offers a significant profit if saving there. However, it does not make members of farmer groups save there; instead, they choose to save in conventional banks. This research aims to determine the factors behind why farmer group members do not save in the KUD Margodadi savings and loan unit, as well as to analyze the level of trust of farmer group members against the KUD Margodadi savings and loan unit. This research is quantitative research with descriptive analysis. The population is all members of farmer groups who do not save in savings and loan units KUD Margodadi, but they save in conventional banks, which is as many as 42 people. The sampling technique used is total sampling with a sample size of 42 people. Data analysis in this research using the formula average count (central tendency) and percentage calculations. This research indicates that the dominant factors that motivate members of farmer groups not to save in KUD Margodadi savings and loan unit are rational factors, and the dominant rational factors are instrumental. Factors that are not dominant are irrational factors. The results of this research indicate that the level of trust of members of farmer groups against savings and loan units KUD Margodadi is classified as high, at 88.1%. Although the level of trust is high, respondents still do not save in the savings and loan unit because the dominant is motivated by rational factors.